Draft Annual Plan 1990-91 Part - II : Plan Proposals in Detail Union Territory of Daman and Diu - Planning Commission (Planning Commission, 1990)
Agriculture is the primary economic activity of the people of Daman and Diu. About one third of the main worker's population are engaged in mainly agriculture. the area available for cultivation is too small i.e. 2,900 hectares which account for 25% of geographical. Out of this 2,600 hectares is in Daman and rest in Diu. The area under food grain crops in Daman is about 2,400 Ha. which is about 33% of the geographical area, 90% of this area is rainfed for which farmers have to be at the mercy of irregular and scanty rains.
Department of Planning and Statistics, Administration of Daman and Diu